EFEKTIVITAS CARA PEMASAKAN TERHADAP KARAKTERISTIK FISIK MASAKAN DAGING BABI HUTAN - Rompis, John E.G; Komansilan, Sylvia (ZOOTEC, 2014)
EFFECTIVITY OF COOKING METHOD ON PHYSICAL CHARACTERISTIC OF COOKERY WILD PIG MEAT. The objective of this study was to evaluate the physical characteristic of cookery wild pig meat with different cooking methods. Research was done using completely randomized design with three treatments of coocing method (bamboo cooker apparatus, stainless cooker apparatus and soil cooker apparatus) and five replications in each treatment. All treatments were added with spicy ingredients of cabai, daun bawang, kamangi, sereh, jahe, and daun jeruk. Physical characteristics were including pH, water content and water holding capacity, analized at animal product technological laboratory. Data were analyzed by analysis of variance model with Duncan statistical test for significant F test. Result study showed that different cooker apparatus affected significantly physical characteristics of cookery wild pig meat in term of pH, water content and water holding capacity. It can be concluded that cooking method using bamboo cooker apparatus yield thye best physical characteristics of cookery wild pig meat. Kata Kunci: Cooker apparatus, physical characteristic, cookery wild pig meat.